Analisis Perbandingan Harga Saham dan Volume Perdagangan Saham Sebelum dan Sesudah Stock Split - Indarti, Iin; Purba, Desti Mulyani BR. (Jurnal Ilmu Ekonomi ASET, 2011)
Stock split is one kind of corporate action implemented by companies inorder to rearrange stock price to be at a more liquid range and provide more positivesignal to investor. The stock split carried out on the basis of two theories. According tothe Trading Range Theory, the high stock price is the driving force for the company tosplit its stock with the hope of increasing the liquidity of stock trading, putting the stockon the optimal trading range and will be more and more investors that will be investing.Signaling Theory states that the stock split is the conveyance of information aboutperformance and prospects to the market. The purpose of this research was to analyzethe differences of stock price and stock trading volume activity pre and post stock splitevent, so that investors could use this event to gain benefit. This research used eventstudy method to observe average stock price, and trading volume activity within fivedays pre and post event date. This research used secondary data collected from IndonesianCapital Market Directory ( ICMD) 2007. The data used in research was taken from : 10days announcement date of stock split applied as event date (to), daily closing price, theamount of daily traded share and the amount of listed share. There were 9 companieswhich implemented stock split policy 2007. Results of the study showed that there weresignificant differences of stock price and trading volume activity from pre and post event.Keywords: stock split, stock price, trading volume activity, trading range theory,signaling theory,and event study.